Pay Differences among the Highly Paid: The Male-Female Earnings Gap in Lawyers' Salaries - Wood, Robert G.; Corcoran, Mary E.; Courant, Paul N. (Journal of Labor Economics, 1993)
This article uses very detailed information on graduates of the University of Michigan Law School to examine male-female pay differences in that population. Men and women in this population have virtually identical human capital on graduation from law school, allowing us to examine carefully the different impact of children and work history on men's and women's careers and earnings. Taking time from work in order to care for children reduces wages significantly, but a rich set of controls, including childcare, work history, school performance, and job setting measures, still leave one-fourth to one-third of the earnings gap unexplained.